1986
DOI: 10.1111/j.1600-0447.1986.tb10606.x
|View full text |Cite
|
Sign up to set email alerts
|

Light treatment of seasonal affective disorder in Switzerland

Abstract: Seasonal Affective Disorder (SAD) has been characterised by two or more depressive episodes in autumn or winter (with remission the following spring or summer), decreased energy, increased sleep, increased appetite, weight gain and carbohydrate craving. SAD patients were identified in a Swiss-German population; 22 participated in a light-therapy protocol (1 week bright white light 2,500 lux or dim yellow light 250 lux, from 06-08 h and 18-20 h). Both observer and self-ratings indicated a significant diminution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
52
1

Year Published

1986
1986
2001
2001

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 172 publications
(55 citation statements)
references
References 15 publications
2
52
1
Order By: Relevance
“…Early trials used bright FSFL as treatment, often in comparison to dim light controls, either incandescent or FSFL (e.g., Hellekson et al, 1986;Isaacs et al, 1988;Rosenthal et al, 1985;Winton et al, 1989;Wirz-Justice et al, 1986). This was partly because of the belief that onset of the condition related to reduced day length, and the treatment was intended to lengthen the apparent day length.…”
Section: Light Therapymentioning
confidence: 99%
“…Early trials used bright FSFL as treatment, often in comparison to dim light controls, either incandescent or FSFL (e.g., Hellekson et al, 1986;Isaacs et al, 1988;Rosenthal et al, 1985;Winton et al, 1989;Wirz-Justice et al, 1986). This was partly because of the belief that onset of the condition related to reduced day length, and the treatment was intended to lengthen the apparent day length.…”
Section: Light Therapymentioning
confidence: 99%
“…The Chronobiology Laboratory o f the Psychiatric University Clinic has been carrying out studies on S A D and light therapy since 1984 [6][7][8][9]. In order to follow the course o f winter depressive phases subsequent to diagnosis o f S A D and participation in a controlled light therapy trial, all these SA D patients (n = 70) received a letter in the summer o f 1989 inviting them to an interview with a psychia trist (B .G.).…”
Section: Subjects and M Eth Od Smentioning
confidence: 99%
“…Different authors reported that SAD patients have a high family load (44-67%) for psychiatric disorders in firstdegree relatives [5][6][7][8]. Allen et al [9] found an equal positive (65%) family prevalence for psychiatric diseases in SAD patients, compared to a control group, consisting of patients with affective disorders without seasonality (59%).…”
Section: Introductionmentioning
confidence: 99%